Evaluation of Olfactory Fossa Depth Using Computed Tomography - Paudel, Sharma; Sah, Ramswarth; Budhathoki, Tekendra; Pandey, Ghanshyam (Journal of Nepal Health Research Council, 2025)
Background: Olfactory fossa is a depression in anterior cranial cavity whose floor is formed by cribriform plate of ethmoid bone and is susceptible to injury during functional endoscopic sinus surgery (FESS), especially when fossa is deep. Understanding of patient’s ethmoid roof anatomy and its possible variations is crucial for countering possible complications during functional endoscopic sinus surgery. So, objective of this study was to evaluate olfactory fossa depth. Methods: In this descriptive cross sectional study, olfactory fossa depth was measured on Computed Tomographic images of 280 patients in the Department of Radiology, Tribhuvan University Teaching Hospital. The data were grouped according to Keros classification and their distributions were analyzed according to side and gender. Association between olfactory fossa depth with different parameters were evaluated with descriptive statistics, independent t-test, ANOVA and Chi-square test. Results: Among 280 participants, 144 were male and 136 female. The mean depth of right and left olfactory fossa was found 5.10 ± 1.58 mm and 5.28 ± 1.62 mm respectively. Keros type II was the most common, found in 209 cases (74.60%) on left side and 194 (69.30%) on right side while type III was the least common. The difference between left and right olfactory fossa depth was significant though it was insignificant between male and female. No significant association was found between Keros type with sides and with gender. Conclusions: Variation in olfactory fossa depth was common. Thus, preoperative assessment of ethmoid roof and Keros type is cruicial for warning the surgeon to minimize the critical complications. Key words: Computed Tomography; olfactory fossa depth; para nasal sinus.